A dinâmica da inserção brasileira no Comércio Internacional nos Anos 2000 : uma análise por conteúdo tecnológico - Torezani, Tomás Amaral (2013)
This dissertation aims to analyze the dynamics of Brazilian trade flows concerning to the period 2000-2011 from a technological perspective. The study refers to both national and subnational (by states) levels. It is argued that technology plays an essential role in determining the competitiveness and the trajectory of economic growth, as well as long-term development of a nation, and that the direction towards which moves a country's productive structure can be deduced from the perspective of its commercial basket and its technological standard. The data shown in this work demonstrate that Brazil, over the 2000s, figured as exporter of low technological contents and importer of technology intensive products. Furthermore, the analysis revealed the existence of large territorial heterogeneity and geographical concentration of Brazilian trade flows, and it was found that the states of the South and Southeast regions concentrate most of both Brazilian's exports and imports of all technological groups studied. The analysis undertaken bequeathed the findings that, during the 2000s, Brazilian economy has specialized in low-tech sectors with classical comparative advantages, committing the country's competitiveness in the long term and defining a perverse pattern of trade, i.e., of low quality, characterized by deficits in high-tech sectors and little sophistication of export basket. However, since Brazilian productive and commercial structures shows great diversity, the nation could reverse this undesirable trend with targeted investments in specific sectors to boost industrial development and improve the quality of its international insertion.